Accelerated and enantioselective synthesis of a library of p-stereogenic urea phosphines - Koshti, Vijay S.; Gote, Ravindra P.; Chikkali, Samir H. (European Journal Of Organic Chemistry, 2018)
Chiral phosphorus ligands play a central role in majority of the asymmetric transformations. However, access to chiral phosphorus ligands is limited due to their challenging synthesis. Reported here is a highly efficient and accelerated catalytic asymmetric synthesis of P-stereogenic urea containing phosphines leading to a small library of 18 chiral phosphorus compounds. Characteristic two doublets in a P-31 NMR spectrum, spectroscopic and analytical evidences authenticated the formation of [Pd-{(S,S) Me-FerroLANE}(m-phenylurea)(I)] complex. Indeed, [Pd-{(S,S) Me-FerroLANE}(m-phenylurea)(I)] was found to catalyze the C-P coupling reaction and quantitative conversion was observed within 18 hours. Under optimized conditions, iodophenyl urea's (2a-2j) were treated with secondary phosphines (1a-1c) in presence of [Pd-{(S,S) Me-FerroLANE}(m-phenylurea)(I)] to obtain P-stereogenic urea phosphines 5a-5r. The identity of these urea derived phosphines was unambiguously ascertained using a combination of spectroscopic and analytical methods. The catalyst tolerated various functional groups and yielded corresponding urea containing phosphines with an enantiomeric excess in the range of 15-62 %.